Innovation in Biology Education: Classroom Action Research as a Catalyst for the Renewal of Teaching Methods in Indonesia - Yamin, Muhammad Richsan; Candy Ponto, Claudia; Claudia Junadi, Eva; Siddhi Fonso, Tiara; Melie Rusli, Vianna (Biology Teaching and Learning, 2024)
Abstract. This study emphasizes the critical importance of enhancing Classroom Action Research (CAR) as a catalyst for more sustainable Biology education. The primary factors identified include a lack of comprehensive information regarding the implementation of CAR across various regions in Indonesia and the current weaknesses inherent in CAR. The objective of this research is to examine the effectiveness of CAR in improving the understanding of biological concepts and to propose a model for sustainable CAR. A systematic review method following the PRISMA approach was employed to analyze relevant studies. The findings reveal that CAR is effective across almost all Biology teaching methods, enhancing quality through student participation, creativity, and learning outcomes. However, the principal challenge lies in the unsustainable nature of CAR, which hampers long-term improvement efforts. This study develops a sustainable CAR design, referred to as Sustainable Action Research (SAR), which encompasses comprehensive planning, monitored implementation, evaluation of outcomes and processes, and reflective practices to develop new strategies. SAR acts as a catalyst for the renewal of Biology teaching methods, enabling educators to adapt to evolving educational challenges. Recommendations for future research include focusing on the implementation of SAR and evaluating its effectiveness. Active teacher involvement in every stage of SAR is essential to ensure that innovations are aligned with on-the-ground needs. Collaboration between academics and teachers is also crucial to improving the quality of education in Indonesia, particularly in the field of Biology education Keywords: classroom action research, sustainable action research, biology education, sustainable education